SUPERVISION OF LABORATORY MEASURING EQUIPMENT BASED ON THE EXAMPLE OF ILLUMINANCE METERS - Banaszak, Agnieszka; Wtorkiewicz, Justyna (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2015)
Laboratory measuring equipment should be subject to supervision. The scope of this supervision depends on the field of the application of the instrument and should include calibration. The correct operation of the instrument is also a crucial factor. It should be proceeded in the proper manner and in right conditions. The instrument may also be subject to periodic inspections, checks and, if necessary, repairs.